2019
DOI: 10.1002/term.2883
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of photocrosslinked gelatin/hyaluronic acid hybrid scaffold for the repair of cartilage defect

Abstract: Summary There is no therapy currently available for fully repair of articular cartilage lesion. Our laboratory has recently developed a visible light-activatable methacrylated gelatin (mGL) hydrogel with the potential for cartilage regeneration. In this study, we further optimized mGL scaffolds by supplementing methacrylated hyaluronic acid (mHA), which has been shown to stimulate chondrogenesis via activation of critical cellular signaling pathways. We hypothesized that the introduction of an optimal ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 61 publications
0
57
0
Order By: Relevance
“…As expected, the softer CS-MeHA hydrogel exhibited a higher degree of swelling and degradation rate compared to the more rigid MeHA hydrogel ( Figure 4 b,c) due to the lower degree of crosslinking of CS-MeHA polymer chains (i.e., the presence of CS pending peptides). It should be noted that, to date, the optimal swelling ratio that could ensure the best clinical results has not been defined [ 47 ]. Regarding hydrogel degradation, since the thiol-methacrylate ester bond is not prone to hydrolysis [ 48 ], MeHA and CS-MeHA hydrogel degradation by the recombinant MMP7 enzyme was attributed to the cleavage of the MMP7-sensitive peptide crosslinker [ 15 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the softer CS-MeHA hydrogel exhibited a higher degree of swelling and degradation rate compared to the more rigid MeHA hydrogel ( Figure 4 b,c) due to the lower degree of crosslinking of CS-MeHA polymer chains (i.e., the presence of CS pending peptides). It should be noted that, to date, the optimal swelling ratio that could ensure the best clinical results has not been defined [ 47 ]. Regarding hydrogel degradation, since the thiol-methacrylate ester bond is not prone to hydrolysis [ 48 ], MeHA and CS-MeHA hydrogel degradation by the recombinant MMP7 enzyme was attributed to the cleavage of the MMP7-sensitive peptide crosslinker [ 15 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gelatin is an ideal copolymer for HA as it provides structural support and RGD-integrin binding sites that allow cell adhesion and proliferation, unlike HA alone [ 32 ]. Gelatin-HA constructs have been studied extensively for regeneration of articular cartilage [ 33 , 34 , 35 ], wound healing [ 36 , 37 , 38 ], and even vocal fold repair [ 39 ] due to their chondrogenic, angiogenic, and cell adhesive properties, and their tunable viscoelastic properties. Like HA, gelatin can be methacrylated, which allows for photopolymerization of gelatin-gelatin or gelatin-HA crosslinks.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…Like HA, gelatin can be methacrylated, which allows for photopolymerization of gelatin-gelatin or gelatin-HA crosslinks. Constructs made of methacrylated gelatin and HA have been shown to suppress hypertrophy and increase GAG expression by embedded, human bone marrow stem cells and, when tested in a full thickness osteochondral defect in rabbits, showed good cartilage regeneration [ 33 ]. Methacrylated HA and methacrylated gelatin can also be 3D bio-printed and polymerized with embedded cells without affecting their viability or chondrogenic properties, making them a good platform for custom, patient-specific cartilage implants [ 35 ].…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…The methods of photopolymerization were based on the use of physical crosslinks, with UV light applied in 17 studies (Bryant & Anseth, 2001; Bryant & Anseth, 2002; Bryant & Anseth, 2003; Buxton et al, 2007; Dua et al, 2016; Elisseeff et al, 2000; Hayami et al, 2016; Lee et al, 2006; Levett et al, 2014; Lin et al, 2017; Neumann et al, 2016; Ramaswamy et al, 2008a; Ramaswamy et al, 2008b; Roberts et al, 2011; Roberts & Bryant, 2013; Sharma et al, 2007; Williams et al, 2003) and VL in 6 studies (Hoshikawa et al, 2006; Kim et al, 2015; Lin et al, 2014; Lin et al, 2019; Pascual-Garrido et al, 2019; Werkmeister et al, 2010). Both synthetic (Bryant & Anseth, 2001; Bryant & Anseth, 2002; Bryant & Anseth, 2003; Buxton et al, 2007; Elisseeff et al, 2000; Hoshikawa et al, 2006; Lin et al, 2014; Neumann et al, 2016; Ramaswamy et al, 2008a; Roberts & Bryant, 2013; Williams et al, 2003) and hybrid photopolymerizable hydrogels (Dua et al, 2016; Hayami et al, 2016; Kim et al, 2015; Lee et al, 2006; Levett et al, 2014; Lin et al, 2017; Lin et al, 2019; Pascual-Garrido et al, 2019; Ramaswamy et al, 2008b; Roberts et al, 2011; Sharma et al, 2007; Werkmeister et al, 2010) have been employed and their use and application are described below.
Fig.
…”
Section: Advances In Approaches Using Photopolymerizable Hydrogels Fomentioning
confidence: 99%
“…Lin et al (Lin et al, 2017) described synergistic effects of chondrogenic preconditioning and mechanical stimulation on bone marrow-derived MSCs in methacrylated HA (MeHA) hydrogels, with superior chondrogenic differentiation in rat osteochondral defects. Lin et al (Lin et al, 2019) reported that methacrylated gelatin (mGL)/MHA enhanced the regeneration of the osteochondral unit in rabbit full-thickness osteochondral defects. Pascual-Garrido et al ( Pascual-Garrido et al, 2019 ) noted that MSCs undergo effective chondrogenesis in a cartilage-mimetic hydrogel using PEG with matrix metalloproteinase 2 (PEG/MMP-2) that can be delivered in vivo and photopolymerized intra-operatively in situ.…”
Section: Advances In Approaches Using Photopolymerizable Hydrogels Fomentioning
confidence: 99%